Evaluation of the Setia Hati Terate Brotherhood Pencak Silat Development Program Bungo Nic.067 Branch - Aldi Indra Kurniawan; Donie; Damrah; Arsil; Heru Andika (Universitas Negeri Semarang, 2024)
One of the coaching processes that is planned, directed, systematic and continuous is a step to achieve peak athlete performance. The existence of fostering the Faithful Hati Terate Brotherhood, Bungo Nic.067 Branch as a forum for fostering and organizing athlete training to achieve achievements. . This study aims to evaluate which includes Context, Input, Process, Product from the Faithful Hati Terate Brotherhood Pencak Silat Development program, Bungo Nic.067 Branch. This program evaluation research uses the CIIP model (context, input, process, product). The subjects of this study include administrators, coaches, athletes. Data collection techniques through 3 ways, namely by 1) interviews, 2) observation, and 3) documentation. The data source studied was the development of the Setia Hati Terate Brotherhood, Bungo Nic.067 Branch. The analysis technique used is an interactive model. The results of the study concluded that: 1) Context, the context coaching program is very clear, has a good background and vision and mission of coaching as a forum for fostering pencak silat and creating athletes who can excel at the national level. 2) Input coaching program, recruiting coaches and athletes in good category based on criteria. The infrastructure is quite good, funding for development comes from the ratification fund for new PSHT residents, Bungo Nic.067 branch. 3) The coaching process, the training process is still not good, the training is not in accordance with the program that the management wants because there is no written training program. 4) Product, the results of PSHT athletes from the Bungo Nic.067 Branch are in the good category because there is an increase in achievement even though they have not reached the set targets.